Helping Professors Grow as They Teach and Advise Graduate Students. (22nd April 2020) - DeVaney, Sharon A.; Borr, Mari; Lee, Young‐A; Spangler, Alice; Wilmarth, Melissa J.; Anong, Sophia
Abstract : The purpose of this article is to share ideas from professors who are teaching graduate courses and advising graduate students. Also, the information could benefit graduate students and anyone who is thinking about earning a graduate degree. Each of the professors stated that an experience during their graduate studies helped them develop their teaching and advising style. Professors discussed the importance of including ethical behavior in their graduate courses and described approaches for including the information. One professor discussed obtaining a graduate degree completely online. The need to meet frequently with graduate students when they are working on their theses or dissertations was noted. Whether or not an adviser should include their graduate students as authors on their own publications was discussed .